Primiparity, class 3 obesity, intention to breastfeed and breastfeeding initiation - Leandro Cordero; Michael R. Stenger; Bradley J. Needleman; Sabrena Noria; Mark B. Landon; Craig A. Nankervis (PLoS ONE, 2025)
Background During the 2013–21 period, 674 primiparous women with Class 3 obesity delivered in our institution. Their antenatal infant feeding preference on admission was: 518 (77%) intended to breastfeed (BF) only, 101 (15%) intended to feed formula only and 55 (8%) intended to BF and formula feed combined. Intention to BF only is a predictor of BF initiation, however, data concerning this relationship is limited. Objective To determine the perinatal variables that influence success or failure of BF among primiparous women with Class 3 obesity who antenatally declared their intention to only BF. Methods Retrospective cohort study of women who delivered live singletons without major malformations at ≥ 34 weeks gestation. Results The 518 women who prenatally intended to BF only, were categorized at discharge as exclusive BF (EBF) 197 (38%), any BF (ABF) 212 (41%) and formula feeding (FF) 109 (21%). A lower prevalence of gestational diabetes (10,17 vs 17%), chronic hypertension (16,31 vs 18%), severe preeclampsia (12,22 vs 30%), cesarean delivery (37,55 vs 55%), late preterm (6,17 vs 14%), neonatal hypoglycemia (8,26 vs 22%) and NICU admission (11,25 vs 20%) was present in the EBF group as compared to ABF and FF. African American women were more likely to only FF. Regression analysis showed that the stronger predictors of failure to initiate BF were public healthcare assistance, African American race, preeclampsia, cesarean delivery, neonatal hypoglycemia, prematurity and NICU admission. Conclusion Among primiparous women with class 3 obesity who intended to BF only but failed to do so, the increased prevalence and severity of maternal and neonatal morbidities are likely obstacles to BF their first infant.